2016
DOI: 10.1186/s12917-016-0666-z
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic tail docking: an overview of abuse and report of an interesting case

Abstract: BackgroundThis paper presents an overview of the global controversies surrounding cosmetic tail docking in puppies, some observed inconsistent practices among dog breeders and Veterinarians in West Africa, and the need for the African Veterinary Profession to take a decisive position on the cosmetic docking procedure.Case presentationAn interesting report of observed complications associated with cosmetic tail docking in a 3 week old male Boerboel is reported alongside the management of the ensuing complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…11 The tail plays a major role in a dog's life; it is not only a social tool but also a support for the vertebral column, as well as an important factor in defaecation. 1,12,13 Mellor and Eyarefe et al reported reduced correct social interaction and hygienic defaecation after tail amputation, being a potential source of concern for owners. 12,13 On this basis, considering the normal appearance of caudal nerves, the authors opted to perform tail stabilisation in first intention with envisaged late amputation in case of non-recovery (rather than performing amputation in first intention with no chance of recovery and possible severe complications or medical treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The tail plays a major role in a dog's life; it is not only a social tool but also a support for the vertebral column, as well as an important factor in defaecation. 1,12,13 Mellor and Eyarefe et al reported reduced correct social interaction and hygienic defaecation after tail amputation, being a potential source of concern for owners. 12,13 On this basis, considering the normal appearance of caudal nerves, the authors opted to perform tail stabilisation in first intention with envisaged late amputation in case of non-recovery (rather than performing amputation in first intention with no chance of recovery and possible severe complications or medical treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, the complication rate of amputation can be as high as 50%, infections being the most frequent complication 11 . The tail plays a major role in a dog's life; it is not only a social tool but also a support for the vertebral column, as well as an important factor in defaecation 1,12,13 . Mellor and Eyarefe et al reported reduced correct social interaction and hygienic defaecation after tail amputation, being a potential source of concern for owners 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…These include long-term loss or impairment of the following tail-related functions in some dogs: counterbalancing actions during complicated movements, as also stabilising the vertebral column and supporting the actions of back muscles; roles in successful and hygienic defecation thereby minimising rectal dilatation, rectal sacculation and faecal incontinence; maintenance of pelvic diaphragm integrity by minimising the risk of perineal hernia; and in females of large breeds, reducing their predisposition to urinary incontinence. Also included are possible acute complications of the procedure itself, such as haemorrhage, necrosis, infection, septicaemia, meningitis and in extreme cases, death [ 126 , 127 ]. Although the prevalence of these negative impacts has not been well documented [ 12 ], it is likely to vary with the proficiency of the docker and how quickly veterinary support is sought when adverse outcomes are recognised [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, primary and secondary legislation exists that governs painful procedures. These documents typically consider that the arguments presented to defend them are insufficient to justify exposing animals to unnecessary suffering [79]. Turning to Latin American countries, Chile has an initiative to add an article to its Law for the Responsible Ownership of Pets and Companion Animals that will sanction devocalization, tail docking, and ear cropping for aesthetic purposes [80].…”
Section: Legislation Regarding Mutilations Of Healthy Animalsmentioning
confidence: 99%